Variations of Renal Artery in Cadavers - Lama, Chhiring Palmu; Pradhan, A. (Nepal Medical College Journal, 2019)
Each kidney is usually supplied by a single renal artery which is a lateral branch of abdominal aorta at the level of L1.The arteries supplying the kidneys show variation in the number, source and branching pattern which also include the presence of an accessory or additional and aberrant renal arteries. The additional renal artery towards the lower pole will cross the corresponding ureter and even cause ureteric obstruction. The segmental branches of renal and additional renal arteries are end arteries thus the accidental damage to these arteries can cause ischemia or necrosis and other pathological conditions. The main objective of this study was to note the variations of the arteries supplying the kidneys. An observational study was conducted on thirty kidneys of fifteen cadavers which included the kidneys of both sides. The study was conducted in Department of Anatomy of Nepal Medical College Teaching Hospital during the period between July 2018 to June 2019 and the variations were recorded as (a) single main renal arteries were found in 80% specimens on both sides (b) early division of main renal arteries were found in 16.66 % on both sides (c) origin of main renal arteries were at higher level on left side in 16.66 % (d) presence of additional renal arteries were found in 20% on both sides. This study will be helpful to cryosurgeons and also to radiologists performing various interventional radiological procedures.